2007
DOI: 10.1007/bf03208384
|View full text |Cite
|
Sign up to set email alerts
|

A healthy economy can break your heart

Abstract: Abstract:Panel data methods are used to investigate how deaths from coronary heart disease (CHD) in the United States vary with macroeconomic conditions. A one-percentage-point reduction in unemployment is predicted to raise CHD mortality by 0.75%, corresponding to almost 3,900 additional fatalities. The increase in relative risk is similar across age groups, implying that senior citizens account for most of the extra deaths. Direct evidence is obtained of a role for decreases in medical interventions treating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(167 citation statements)
references
References 55 publications
10
150
3
4
Order By: Relevance
“…This is not surprising since many studies have found that males and females react differently to changes in the economy (Ruhm 2003(Ruhm , 2005Ásgeirsdóttir et al 2013, 2014aDave and Kelly 2012;Tapia Granados 2005b;Birgisdóttir et al 2017). Our results are in contrast to some recent literature on the subject where both pro-and countercyclical relationships have been found (Ruhm 2000;Neumayer 2004;Gerdtham and Ruhm 2006;Ruhm 2003Ruhm , 2005Ruhm , 2007Svensson 2010Svensson , 2007Gerdtham and Johannesson 2005).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is not surprising since many studies have found that males and females react differently to changes in the economy (Ruhm 2003(Ruhm , 2005Ásgeirsdóttir et al 2013, 2014aDave and Kelly 2012;Tapia Granados 2005b;Birgisdóttir et al 2017). Our results are in contrast to some recent literature on the subject where both pro-and countercyclical relationships have been found (Ruhm 2000;Neumayer 2004;Gerdtham and Ruhm 2006;Ruhm 2003Ruhm , 2005Ruhm , 2007Svensson 2010Svensson , 2007Gerdtham and Johannesson 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Comparably, one does not expect to see much variation in diseases that are mostly genetically determined or take a long time to materialize, such as certain types of cancer, but rather in diseases that are affected by behaviour, lifestyle, and environmental factors. Ruhm (2000Ruhm ( , 2003Ruhm ( , 2005Ruhm ( , 2007, utilizing US data from 1972 through 2000, shows state-level mortality rates to be procyclical, indicating that recessions are beneficial to population health. He speculates that rising opportunity costs may be an explanation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As research by Ruhm,6 7 myself8 9 and others10 11 has shown, using data from a variety of market economies, economic expansions raise total mortality and cardiovascular deaths which, conversely, fall in recessions. Applying Ruhm estimates6 7 to the 2.5 million annual deaths observed in recent years in the USA, an economic recovery (ie, an expansion) reducing the unemployment rate from, say, 9% to 4%, is expected to be associated with some 60 000 extra deaths, of which almost a third would be heart attacks. In spite of the conclusions reached by Stuckler, this is what the historical experience suggests.…”
mentioning
confidence: 95%